Pemulihan Berat Badan Balita Gizi Kurang melalui Pendampingan dan Pemberian Makanan Tambahan di Wilayah Kerja Puskesmas Jembatan Kecil Kota Bengkulu - Simbolon, Demsa; Alfatah Reza Purqon; Champaca Putri; Desi Fitria Anggriani; Dhea Riski Putri Indana; Helen Albaina; Melinda Sari; Meysin Cicilia; Mia Meisara; Nova Anjelina; Putri KatrimaNingsih; Yendea Dwi Agustin; Yulia Anjelita (ADM : Jurnal Abdi Dosen dan Mahasiswa, 2025)
Malnutrition in toddlers is a significant health problem, especially in the working area of the Jembatan Kecil Health Center, Bengkulu City, with a prevalence of 0.8%. Factors such as limited access to health services, minimal nutrition education, and family economic conditions also affect this problem. The impact of malnutrition is very large, affecting children's physical health and cognitive development. The purpose of this service is to improve the nutritional status of toddlers and pregnant women in SEZs through assistance and provision of supplementary food (PMT). The method used is a comprehensive nutrition intervention approach, targeting undernourished toddlers aged 6-60 months and pregnant women with KEK. The activity began with village community deliberations (MMD) and continued with the measurement of nutritional status and the provision of nutrition education and PMT. The assistance was carried out for 3 days, with monitoring of the nutritional development of toddlers and pregnant women. The results showed an average weight increase of 0.1 kg after PMT in the form of formula milk. Although the increase in maternal knowledge about nutrition is quite significant, there are challenges in the implementation of education due to attention disorders due to children's conditions. Nevertheless, education to pregnant women in SEZs has succeeded in increasing their knowledge about nutrition. In conclusion, mentoring and providing PMT in a targeted manner can improve the nutritional status of toddlers and parental awareness, although it requires continuous efforts in monitoring and education for more optimal results.